2003
DOI: 10.1007/s00213-003-1537-4
|View full text |Cite
|
Sign up to set email alerts
|

Castration in rats impairs performance during acquisition of a working memory task and exacerbates deficits in working memory produced by scopolamine and mecamylamine

Abstract: These results indicate that castration in male rats impairs working memory during acquisition of a spatial maze task. Additionally, these results suggest that the absence of testicular hormones increases the sensitivity of male rats to the impairing effects of scopolamine as well as mecamylamine on working memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 36 publications
4
53
5
Order By: Relevance
“…Like effects on the spatial working memory processes of the medial prefrontal cortex demonstrated previously (Daniel et al, 2003;Kritzer et al, 2007;Kritzer et al, 2001), the adverse effects of GDX on the NOR task observed here were attenuated by supplementing GDX animals with TP but not E, and were significantly correlated with a bioassay of circulating androgens--BSM weight. Although not examined in this study, there are several reasons to suspect that correlations previously found between the effects of GDX on medial prefrontal working memory function and on the density of its functionally critical dopamine (DA) innervation (Kritzer et al, 2007) may also extend to the perirhinal-dependent processes of the NOR task, since the effects of GDX on DA innervation in perirhinal prefrontal fields are qualitatively and quantitatively similar to those observed in medial prefrontal areas and are likewise androgen dependent (Kritzer et al, 2003), and because performance on NOR tasks, like that of the medial prefrontal cortical-mediated spatial working memory (Stam et al, 1989;Zahrt et al, 1997) is also impaired by selective perturbations of the prefrontal dopamine system (Morrow et al, 2000).…”
Section: Summary Conclusion and Future Directionssupporting
confidence: 69%
See 2 more Smart Citations
“…Like effects on the spatial working memory processes of the medial prefrontal cortex demonstrated previously (Daniel et al, 2003;Kritzer et al, 2007;Kritzer et al, 2001), the adverse effects of GDX on the NOR task observed here were attenuated by supplementing GDX animals with TP but not E, and were significantly correlated with a bioassay of circulating androgens--BSM weight. Although not examined in this study, there are several reasons to suspect that correlations previously found between the effects of GDX on medial prefrontal working memory function and on the density of its functionally critical dopamine (DA) innervation (Kritzer et al, 2007) may also extend to the perirhinal-dependent processes of the NOR task, since the effects of GDX on DA innervation in perirhinal prefrontal fields are qualitatively and quantitatively similar to those observed in medial prefrontal areas and are likewise androgen dependent (Kritzer et al, 2003), and because performance on NOR tasks, like that of the medial prefrontal cortical-mediated spatial working memory (Stam et al, 1989;Zahrt et al, 1997) is also impaired by selective perturbations of the prefrontal dopamine system (Morrow et al, 2000).…”
Section: Summary Conclusion and Future Directionssupporting
confidence: 69%
“…Recent studies in adult male rats have identified modulatory roles for gonadal steroids on working memory and other types of cognitive tasks that are known to be sensitive to lesions of the medial (Ceccarelli et al, 2001;Daniel et al, 2003;Kritzer et al, 2007;Turvin et al, 2007) and orbital (Kheramin et al, 2003;Kritzer et al, 2007) divisions of the prefrontal cortices in rats. The studies presented here now demonstrate gonadal hormone sensitivity for a spontaneous NOR task that is sensitive in part to lesions of the third major subdivision of the rat PFC -the perirhinal prefrontal cortices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, broad conclusions are more difficult to draw. In general, the bulk of evidence suggests that gonadectomy impairs memory in males tested in the radial arm maze, T-maze, Barnes Maze, and object recognition tasks, as well as several operant tasks that test prefrontal cortex function (Ceccarelli et al 2001;Kritzer et al 2001Kritzer et al , 2007Daniel et al 2003;Sandstrom et al 2006;Aubele et al 2008;Gibbs and Johnson 2008;Spritzer et al 2008;Locklear and Kritzer 2014). However, the deleterious effect of gonadectomy does not extend to all types of memory, particularly spatial reference memory tested in the Morris water maze (Gibbs 2005;Sandstrom et al 2006;Spritzer et al 2008).…”
Section: Effects Of Exogenous E 2 On Memory In Malesmentioning
confidence: 99%
“…Whereas these researches have primarily focused on estrogen in females, recent evidence suggested that testosterone can also modulate learning and memory in males through its stimulation of the hippocampal neurons (Daniel et al, 2003;Hajszan, 2007 ;Leonard et al, 2007). Animal studies suggested that sex hormones play a role in the organization of the nervous system and memory.…”
Section: Introductionmentioning
confidence: 99%